Book review “The dreamkeepers: an invictus mystery thriller” by Antonio Zadra - Schredl, Michael (International journal of dream research, 2020)
The book, by Antonio Zadra, includes recurrent dreams, lucid dreaming, nightmares, violence, evil creatures, and the dreamkeepers’ task is to ensure that the dreamworld is free of oppression and terror. Several oneironauts, like James Dillan, Vincente Santilli (in the footsteps of his mother) and Michael Kohler, are trying to outwit the dark forces that try to take over the dreamworld and rule mankind. Overall, the book is well-written and is gripping from beginning to end.